Predictors of time to cough resolution in children with chronic wet cough treated with antibiotics after bronchoscopy. Issue 12 (9th September 2019) - Wong, Oi Yin; Marchant, Julie M.; Yerkovich, Stephanie T.; Chang, Anne B.
Abstract: Background: Chronic wet cough is common in pediatric pulmonology practice and is clinically important. Guidelines recommend treatment with antibiotics as their effectiveness has been proven. However, factors associated with duration of cough in response to antibiotics in children with chronic wet cough have not been prospectively examined. Objective: To determine if demographic, clinical and/or bronchoalveolar lavage (BAL) factors are associated with "time to cough resolution" in children with chronic wet cough treated with antibiotics after bronchoscopy. Methods: Data from children with chronic wet cough treated with antibiotics after bronchoscopy were extracted from a prospective cohort study database. Cough dairies were used to determine when the cough resolved. Associations between various factors with "time to cough resolution" were examined using regression. Results: The median age of the 133 children was 2.4 years (interquartile range, 1.4‐4.9). Duration of prior cough at bronchoscopy was significantly positively related with "time to cough resolution" ( β  = .010; 95% confidence interval, 0.004‐0.017; P  = .002). This translated to; for each month of prior cough, it took an extra 1.02 days to achieve cough resolution while on antibiotic treatment. Gender, age, diagnosis, tobacco smoke exposure, pneumonia history, blood cellularity, and BAL cellular and microbiology profiles were not significantly associated with time to cough resolution. Conclusion: In children with chronic wet cough, duration of cough before antibiotic treatment is a small but significant determinant of "time to cough resolution." Research using standardized antibiotic regimes is required to provide clinical and/or biomarkers that can further identify factors associated with the response of chronic cough to antibiotic treatment.